Polariton entering a continuum: giant diffuse polaritonic resonance - Moiseyev, Nimrod; Vendrell, Oriol; Cederbaum, Lorenz S.; Šindelka, Milan (Physical review, 2022)
Polaritons arise due to a light-matter interaction and have been amply investigated for atoms and molecules in a quantum field. By increasing the coupling between the atom/molecule and the cavity, the upper polariton penetrates into the continuum (i.e., ionization continuum of atoms or molecules or dissociation continuum of molecules) within the standard two-level approach. We investigate what happens to the polaritons in reality. We first show that the upper polariton cannot enter the continuum if the atomic or molecular system itself does not support metastable states, often called resonances, and instead becomes a giant diffuse bound polariton which can be extended in space to any size one wishes. Then, we show how external perturbations can enable such a diffuse polariton to penetrate into the continuum and turn it into a metastable polariton, i.e., into a polaritonic resonance. In order to achieve these results the coupling of the bound states to the continuum induced by the quantum light has to be taken into account. We discuss how such giant diffuse bound polaritons as well as polaritonic resonances including their finite lifetime can be calculated and present explicit numerical examples. The results provide a complete picture of what happens to the upper polariton in the vicinity of the continuum and may be utilized to enhance ionization or dissociation inside the cavity.
Gesehen am 08.11.2023